Studies on the free-living marine nematodes from Hokkaido, III - Kito, K. (Jour. Fac. Sci. Hokkaido Univ. Ser. VI, Zool., 1978)
Locality: Oshoro, Hokkaido, Japan; Cabinet:
Locality: Oshoro, Hokkaido, Japan; Cabinet:; NeMys doc_id: 7128